RNA Interference Analysis Reveals the Positive Regulatory Role of Ferritin in Testis Development in the Oriental River Prawn, Macrobrachium nipponense - Jin, Shubo; Fu, Hongtuo; Jiang, Sufei; Xiong, Yiwei; Qiao, Hui; Zhang, Wenyi; Gong, Yongsheng; Wu, Yan (Frontiers in Physiology, 2022)
Ferritin plays an essential role in organismic and cellular iron homeostasis in Macrobrachium nipponense. In this study, we aimed to further investigate the role of ferritin in the sexual development of male M. nipponense. According to qPCR analysis of different tissues and developmental stages, ferritin exhibited high expression levels in the testis and androgenic gland, from post-larval developmental stage 5 (PL5) to PL15, indicating it may be involved in gonad differentiation and development, especially in male sexual development. In situ hybridization and qPCR analysis in various reproductive cycles of the testis indicated that ferritin may play an essential role in spermatogonia development in M. nipponense. RNAi analysis revealed that ferritin positively affected mRNA expression of the insulin-like androgenic gland (Mn-IAG) and the secretion of testosterone, and thus positively affected testis development in M. nipponense. This study highlighted the functions of ferritin in the sexual development of male M. nipponense, and provided important information for the establishment of a technique to regulate the process of testis development in M. nipponense.